NAIP proteins are required for cytosolic detection of specific bacterial ligands in vivo - Rauch, Isabella; Tenthorey, Jeannette L; Nichols, Randilea D; Al Moussawi, Khatoun; Kang, James J; Kang, Chulho; Kazmierczak, Barbara I; Vance, Russell E (The Journal of experimental medicine, 2016)
NLRs (nucleotide-binding domain [NBD] leucine-rich repeat [LRR]-containing proteins) exhibit diverse functions in innate and adaptive immunity. NAIPs (NLR family, apoptosis inhibitory proteins) are NLRs that appear to function as cytosolic immunoreceptors for specific bacterial proteins, including flagellin and the inner rod and needle proteins of bacterial type III secretion systems (T3SSs). Despite strong biochemical evidence implicating NAIPs in specific detection of bacterial ligands, genetic evidence has been lacking. Here we report the use of CRISPR/Cas9 to generate Naip1(-/-) and Naip2(-/-) mice, as well as Naip1-6(Δ/Δ) mice lacking all functional Naip genes. By challenging Naip1(-/-) or Naip2(-/-) mice with specific bacterial ligands in vivo, we demonstrate that Naip1 is uniquely required to detect T3SS needle protein and Naip2 is uniquely required to detect T3SS inner rod protein, but neither Naip1 nor Naip2 is required for detection of flagellin. Previously generated Naip5(-/-) mice retain some residual responsiveness to flagellin in vivo, whereas Naip1-6(Δ/Δ) mice fail to respond to cytosolic flagellin, consistent with previous biochemical data implicating NAIP6 in flagellin detection. Our results provide genetic evidence that specific NAIP proteins function to detect specific bacterial proteins in vivo.